P3_5 Balloon Mayhem in Gotham - Patel, Jessica; Patel, Poonam; Joshi, Rutambhara (Physics Special Topics, 2014)
The article investigates how high weather balloons made of helium rise before they burst and drop down to the Earth. Considering the pressure at higher altitudes, the radius of the balloon and the mass of the package we find that the balloon rises to an altitude of 37800m.